2018
DOI: 10.1159/000494168
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNA Expression Profiling and Target Prediction in Patients Receiving Dexmedetomidine

Abstract: Background/Aims: Circulating miRNAs could serve as biomarkers for diagnosis or prognosis of heart diseases and cerebrovascular diseases. Dexmedetomidine has protective effects in various organs. The effects of dexmedetomidine on circulating miRNAs remain unknown. Here, we investigated differentially expressed miRNA and to predict the target genes of the miRNA in patients receiving dexmedetomidine. Methods: The expression levels of circulating miRNAs of 3 patients were determined through high through-put miRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 50 publications
1
11
0
1
Order By: Relevance
“…Furthermore, it was indicated that hsa-miR-4508 was a significant highly expressed miRNA in exosomes. It has been reported that circulating hsa-miR-4508 was significantly upregulated in acute myocardial infarction [ 37 ] and patients receiving dexmedetomidine [ 38 ]. However, its functions remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was indicated that hsa-miR-4508 was a significant highly expressed miRNA in exosomes. It has been reported that circulating hsa-miR-4508 was significantly upregulated in acute myocardial infarction [ 37 ] and patients receiving dexmedetomidine [ 38 ]. However, its functions remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are one family of small non‐coding RNAs that regulate gene expression post‐transcriptionally, generally by binding to specific motifs in the 3’‑untranslated regions (3’UTRs) of target genes Bartel, (2009). MicroRNAs coordinate diverse biological events, including differentiation, apoptosis, proliferation, reproduction, stress response, metabolism, immune response and stem cell maintenance (Beitzinger et al., 2007; Gangaraju & Lin, 2009; Huang et al., 2011; Zhang et al., 2013; Junhua et al., 2017; Yang, Chen, et al., 2018). MicroRNAs have been shown to play an important role in the acquisition and maintenance of male fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, microRNAs (miRNAs) have been revealed to play vital roles in modulating pain transmission in animal experiments and clinical studies (Dai et al., 2019). For instance, hsa‐miR‐101‐3p has been identified as one of the seven miRNAs that were reduced after delivery of Dex to the subjects (Yang et al., 2018). The neuroprotective role of miR‐101 has been underscored in Alzheimer's disease (Vilardo, Barbato, Ciotti, Cogoni, & Ruberti, 2010).…”
Section: Introductionmentioning
confidence: 99%